A Turkish BCS1L mutation causes GRACILE-like disorder - Serdaroğlu, Esra; Takcı, Şahin; Kotarsky, Heike; Çil, Onur; Utine, Eda; Yiğit, Şule; Fellman, Vineta (The Turkish Journal of Pediatrics, 2016)
A full-term growth-restricted female newborn (1790 g), presented with lactic acidosis (12.5 mmol/L) after birth. She had renal tubulopathy, cholestasis and elevated serum ferritin concentration (2819 ng/ml). Two similarly affected sisters had died before 3 months of age. Mitochondrial disorder was suspected since the disease resembled the Finnish GRACILE syndrome, caused by a homozygous mutation (c.232A > G) in BCS1L. Thus, we sequenced the BCS1L gene, encoding the assembly factor for respiratory chain complex III. The patient had a homozygous mutation (c.296C > T; p.P99L), for which both parents were heterozygous. In four previously published patients of Turkish origin, the same homozygous mutation resulted in complex III deficiency, tubulopathy, encephalopathy, and liver failure. The p.P99L mutation seems to be specific to Turkish population and leads to GRACILE-like or Leigh-like condition. Assembly defects in complex III should be investigated in the affected tissues, since fibroblasts may not exhibit the deficiency.
Keywords: BCS1L mutation; GRACILE; Turkish